Employability skills of graduates: Insights from job advertisements - Suleman, F. (2021)
This paper examines online job advertisements to identify the type of skills and other attributes required for higher education graduates in European countries. The data were collected from European job websites in 2019 (n=1,752) for any country and occupation having a job offer requiring higher education. The empirical analysis starts with a fuzzy clustering to identify typical skill patterns required by employers. Six clusters emerge from the data; five can be labelled as adaptability skills, foreign languages, specific skills, work attributes, and managing skills. The remaining one is referred to as null cluster with no distinctive required skill. Subsequently, we examine the occupation and employment conditions associated with each fuzzy cluster. Despite the demand for graduates, the service and sales related occupations prevail in the null cluster. In other five well-defined clusters we find a mix of skills of some high-qualified occupations, and search for specific skills acquired through work experience.The findings raise the question about the assignment of graduates in less qualified occupations.